Effects of nitridation on SiC/SiO2 structures studied by hard X-ray photoelectron spectroscopy. (27th May 2020) - Berens, Judith; Bichelmaier, Sebastian; Fernando, Nathalie K; Thakur, Pardeep K; Lee, Tien-Lin; Mascheck, Manfred; Wiell, Tomas; Eriksson, Susanna K; Matthias Kahk, J; Lischner, Johannes; Mistry, Manesh V; Aichinger, Thomas; et al.
Abstract: SiC is set to enable a new era in power electronics impacting a wide range of energy technologies, from electric vehicles to renewable energy. Its physical characteristics outperform silicon in many aspects, including band gap, breakdown field, and thermal conductivity. The main challenge for further development of SiC-based power semiconductor devices is the quality of the interface between SiC and its native dielectric SiO2 . High temperature nitridation processes can improve the interface quality and ultimately the device performance immensely, but the underlying chemical processes are still poorly understood. Here, we present an energy-dependent hard x-ray photoelectron spectroscopy (HAXPES) study probing non-destructively SiC and SiO2 and their interface in device stacks treated in varying atmospheres. We successfully combine laboratory- and synchrotron-based HAXPES to provide unique insights into the chemistry of interface defects and their passivation through nitridation processes.